Intraocular Amphiregulin antibody and axial elongation in nonhuman primates - Wang, Wenyao; Nan, Yan; Huang, Tiejun; Pu, Mingliang; Jonas, Jost B. (Frontiers in Ophthalmology, 2022)
Purpose: To examine the effect of intraocularly applied amphiregulin antibody on physiological axial elongation in young nonhuman primates. Methods: The experimental study included six male 12-months-old macaque nonhuman primates (body weight:2.46±0.25kg;range:2.20-2.90kg). In the experimental group (n=3 animals), three intravitreal injections of amphiregulin antibody (100μg/50μl) were applied to the left eyes at intervals of 4-6 weeks, and injections of phosphate buffered solution (50μl) were applied to the right eyes. Three other animals were assigned to a blank control group. Results: During the study period of 23.6 weeks, axial length in the experimental group did not change in the left eyes (18.91±0.37mm to 18.94±0.67mm;P=0.90), while it linearly increased in the right eyes (18.87±0.38mm to 19.24±0.53mm;P=0.056) and in the control group (left eyes:19.15±0.22mm to 19.48±0.22mm;P=0.009; right eyes:19.17±0.15 mm to 19.46±0.23 mm;P=0.024). The interocular difference in axial elongation increased in the experimental group from -0.11±0.12mm at 4 weeks after baseline to -0.34±0.15mm at the study end, while in the control group, the interocular side difference did not change significantly (from 0.01±0.10 mm to 0.03±0.08 mm;P=0.38). The difference in the interocular difference in axial elongation between the two groups was significant at 8 weeks (P=0.01), 15 weeks (P=0.007), and at study end (P=0.02). The interocular difference in axial length correlated with the interocular difference in vitreous cavity length (standardized regression coefficient beta:0.85;P<0.001). The interocular axial length difference was inversely associated with the interocular refractive error difference (beta:-0.49;P<0.001). Conclusions: Intraocularly applied amphiregulin antibody (100μg) reduced the physiological ocular axial elongation in juvenile nonhuman primates.